Design of United Identity Authentication and Key Agreement Protocol for Hybrid Cloud - Chongxia Wang; Meizhen Gao; Qian Liu; Xianwei Zhou (Dianxin kexue)
Aiming at the heterogeneous users and the inconsistent authentication mechanism for hybrid clouds, a design of united identity authentication and key agreement protocol for hybrid cloud was proposed based on bilinear pairings and key agreement mechanism, which could realize the distributed management and dynamic acquisition of security information of authentication and authorization policy. The theoretical analysis and experiment results show that the proposed protocol is safe and efficient, which can effectively prevent data tampering, identity forging, replay attacks and man-in-the-middle attacks. Else the proposed protocol provides a practical solution on identity authentication and key agreement in hybrid clouds with less computation and communication overheads.